The Impact of Global Climate Change to Climate Condition of Bengkulu Watershed, Indonesia - Faski Gita Ivana Suci Lestari (EDP Sciences, 2021)
Global climate change that occurred in this century can affect the pattern of rain and increase in temperature on earth. This study aims to determine and analyze the increase in rainfall, air temperature, potential evapotranspiration and actual evapotranspiration in the Bengkulu watershed. For this reason, the regional rainfall is calculated using the Thiessen Polygon, the mean air temperature of the watershed based on the median elevation, potential evapotranspiration using the Thornthwaite Method and actual evapotranspiration using the basis of the difference in rainfall to potential evapotranspiration. The results showed that every year there was an increase in rainfall, air temperature, potential evapotranspiration and actual evapotranspiration in the Bengkulu Watershed. In the 2009-2013 period, the average annual rainfall of 3,581 mm increased to 3,641 mm in the 2014-2018 period. For air temperature, the average monthly air temperature in the Bengkulu Watershed for the 2009-2013 period was 25.8°C, while the air temperature in the 2014-2018 period was 26.1°C. This means that in a period of 5 years there is an increase in temperature of 0.3°C. Furthermore, due to the increase in air temperature, there was an increase in the average monthly potential evapotranspiration from the 2009-2013 period to the 2014-2018 period, namely from 1,493 mm to 1,537 mm, while for actual evapotranspiration there was an increase from 1,486 mm to 1,518 mm.